Beyond localization: from hodology to function - ffytche, Dominic H (The Royal Society, 2005)
A century on, Campbell's largely forgotten 1905 monograph on the localization of cerebral function has a distinctly contemporary feel. Although his map of cortical fields has been eclipsed by Brodmann's later contribution, Campbell's project went beyond cytoarchitectonic cartography, attempting to integrate clinical, anatomical and physiological evidence to provide a guide to function. A key component of Campbell's integrative, functional anatomical approach was hodology—the pattern of white matter connections between cortical areas—foreshadowing a recently developed functional anatomical technique: diffusion tensor tractography. Here, we revisit Campbell's model of the human visual system using tractography to illustrate prominent white matter connections within the occipital lobe and from occipital to frontal, parietal and temporal regions. Campbell used his integrative approach to support the view that vision consisted of a ‘visuo-sensory’ and a ‘visuo-psychic’ stage, combining hodological, cytoarchitectonic, physiological and clinicopathological evidence to locate the former within the calcarine cortex and the latter within the cortical field surrounding it. Speaking directly to contemporary debates surrounding the neurobiology of conscious vision and providing a framework with which to shape future developments in tractography, Campbell's integrative functional anatomical approach is as relevant today as it was 100 years ago.